1997
DOI: 10.1002/qj.49712353804
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of the asian summer monsoon to aspects of sea‐surface‐temperature anomalies in the tropical pacific ocean

Abstract: The response of both the time of onset, and the strength of the Asian summer monsoon, to regional aspects of the sea surface temperature (SST) anomalies in the tropical Pacific Ocean associated with El Nifio/Southern Oscillation (ENSO) has been investigated through a series of sensitivity experiments with the Universities' Global Atmospheric Modelling Programme (UGAMP) General Circulation Model (UGCM). This paper builds on the work of Ju and Slingo (1995) and on their hypothesis that the relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(81 citation statements)
references
References 18 publications
(2 reference statements)
3
78
0
Order By: Relevance
“…2). Long-term variability (thousands of years) of the mid-latitude westerlies and the South Asian summer monsoon is linked to changes in Northern Hemisphere insolation, while shorter-term variability (years to decades) is attributed to changes within the climate system, such as variation in Eurasian snow cover, the El Niñ o-Southern Oscillation, and tropical sea surface temperatures (Hahn and Shukla, 1976;Dey and Bhanu Khumar, 1982;Dickson, 1984;Sirocko et al, 1991;Prell and Kutzbach, 1992;Soman and Slingo, 1997;Bush, 2000Bush, , 2002Rupper, 2007). In addition, model results suggest that recent anthropogenic forcing (e.g.…”
Section: Physical Settingmentioning
confidence: 99%
“…2). Long-term variability (thousands of years) of the mid-latitude westerlies and the South Asian summer monsoon is linked to changes in Northern Hemisphere insolation, while shorter-term variability (years to decades) is attributed to changes within the climate system, such as variation in Eurasian snow cover, the El Niñ o-Southern Oscillation, and tropical sea surface temperatures (Hahn and Shukla, 1976;Dey and Bhanu Khumar, 1982;Dickson, 1984;Sirocko et al, 1991;Prell and Kutzbach, 1992;Soman and Slingo, 1997;Bush, 2000Bush, , 2002Rupper, 2007). In addition, model results suggest that recent anthropogenic forcing (e.g.…”
Section: Physical Settingmentioning
confidence: 99%
“…The observed SST anomalies are computed from the Hadley Centre sea ice and SST (HadISST) data set (Rayner et al, 1996). The Niño 3.4 index is preferred over the Southern Oscillation Index (SOI) as it represents the ENSO phenomenon more compactly (Soman and Slingo, 1997). This SST index makes it easier for comparison purposes with the IODZMI that is also SST based.…”
Section: Enso Datamentioning
confidence: 99%
“…The relationship between ENSO and the monsoon has noticeably weakened after 1976 (Kumar et al, 1999;Kinter et al, 2002). Moreover, using an atmospheric general circulation model, the influence of ENSO on the SASM was investigated by Ju and Slingo (1995) and Soman and Slingo (1997). They concluded that the latitudinal position of the ITCZ is significantly influenced by ENSO, and as a consequence, the convective rainfall over the VCH is associated with the ITCZ.…”
Section: Introductionmentioning
confidence: 99%